AKSIOLOGI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK GENERASAI DIGITAL BERKARAKTER ISLAM - Indra Mulhim Hidayat Nasution; Panigoran Rangkuti; Herlini puspika sari (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to analyze the role and axiological values of Islamic Religious Education (PAI) in shaping the character of the digital generation with Islamic morality. The development of digital technology has had a significant impact on the behavior and values of young people; therefore, religious education must play a strategic role in maintaining morality amid the currents of globalization. This research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation involving teachers and students of Islamic senior high schools implementing digital-based learning. The findings reveal that the axiology of PAI serves as a foundation of values and ethics that guide the educational direction—not only toward cognitive achievement but also moral and spiritual formation. The implementation of Islamic axiological principles through innovative learning strategies and Islamic digital literacy has proven effective in strengthening students’ character in both virtual and real-life contexts. This study concludes that the integration between Islamic values and technology is essential for shaping a digital generation that is intelligent, ethical, and spiritually grounded.